Trajetórias e experiências de mulheres na Reitoria da UFPB - Santiago, Stella Marcia de Morais (2021)
The research Trajectories and life experiences of women in the UFPB Rectory sheds light on the challenges faced by women in the face of historical patriarchal ties that hinders gender equality relations, marked by political engendering, almost always constituted by a demarcation of male power in the academic society. This thesis focused on the career trajectory of the dean women at the UFPB, a research field. Its central question stems from the following question: Who are the women who became the dean of the UFPB, and how did their career ascension process take place? The research objective is to understand the career trajectories and life experiences of women in positions/functions of dean, vice-deans and associate deans of university management at UFPB, based upon gender crossings and political engendering experienced in these places. It also consists in pointing out representative elements of gender crossings, and power that they experienced institutionally; identify aspects that configure the managerial identity and the learning constituted by these women in the positions/functions they occupied; present and analyze the narratives of their trajectories and experiences as women who reached the highest level, the university rectory. Regarding the methodological aspects, this research used the narrative approach, supported by the life histories, interviews and the training method, to tell the career trajectories of personal and professional life that marked their itinerary. The interviewees are the professors who worked in the university rectory, and reached the most substantial level of authority over the UFPB academic administration, as dean, vice-deans and associate deans. For the analysis and interpretations in the composition of meanings, we used the interviews obtained from six women as the main source, in which we collected and recorded their stories, and consulted their resumes as a complementary source. The reading of their narratives demonstrates how their academic-professional life testimonies are delineated from the positions/functions they have occupied in the university rectory, despite the gender crossings and political engendering they have faced in the academic society.